The impact of trailing edge flap on the aerodynamic performance of small-scale horizontal axis wind turbine - Mansi, Aktham; Aydin, Devrim (Pergamon-Elsevier Science Ltd, 2022)
Despite the significant progress in the wind energy field, there is always space for new blade profiles to improve the efficiency and the energy extracted of HAWTs. To improve the performance of small-scale HAWTs, a new blade profile design using a fixed trailing-edge flap was investigated using blade element momentum (BEM) approach and validated using computational fluid dynamics (CFD) approach. The aim of this study is to obtain a new blade profile which has higher lift-to-drag coefficient for wind turbine by integrating a trailing-edge flap into a reference blade design. To determine the optimal blade profile, the annual yield based on the Weibull distribution is used. The full three-dimensional CFD analyses were performed on the new blade profile only. The BEM results show that at the design tip speed ratio of 7, the power coefficient of the new blade profile is 8.3% higher than the reference design. According to the new blade profile, the CFD method over-predicts the power coefficient compared with the BEM method. According to wind speed distribution in Turkey, the annual yield of the wind turbine with the reference blade profile and the new blade profile was found as 6378 kWh/year and 6944 kWh/year, respectively.
Keywords: QBlade; Wind turbine; Blade element momentum (BEM); Computational fluid dynamics (CFD); Trailing edge flap